Economics of resources, agriculture, and food - Seitz, Wesley D. (McGraw-Hill, 1994)
This book is about: Economic scope, Organization, and problems of agriculture; MIcroeconomic concepts; Markets; Macroeconomic relationships; Public policy and agriculture.